Założenia budowy i funkcjonowania organizacji sieciowej w turystyce - Perechuda, Kazimierz; Nawrocka, Elżbieta (The methodological assumptions of the functioning of the net tourist companies, 2006)
In the paper are presented: the necessity to change the methodological approach in the scientific research of the tourist companies, the reasons to introduce net methodology in the research process of the tourist offices.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 139-144